2005
DOI: 10.1038/nature04184
|View full text |Cite|
|
Sign up to set email alerts
|

The zebrafish dorsal axis is apparent at the four-cell stage

Abstract: A central question in the development of multicellular organisms pertains to the timing and mechanisms of specification of the embryonic axes. In many organisms, specification of the dorsoventral axis requires signalling by proteins of the Transforming growth factor-beta and Wnt families. Here we show that maternal transcripts of the zebrafish Nodal-related morphogen, Squint (Sqt), can localize to two blastomeres at the four-cell stage and predict the dorsal axis. Removal of cells containing sqt transcripts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 27 publications
6
141
0
1
Order By: Relevance
“…Early zebrafish development has not yet been sufficiently probed, despite the recent discovery of interesting ''orphan'' pathway members such as endoplasmic reticulum ion transporters (Kreiling et al, 2008) and evidence indicating the dorsalventral axis is established at the second cleavage (Gore et al, 2005). Moving forward will require increased collaboration among labs with expertise in specific pathways and model systems to cross-check their pathways in a wider variety of taxa, and remaining open to the idea that the origin problem is not yet solved.…”
Section: Major Open Issuesmentioning
confidence: 99%
“…Early zebrafish development has not yet been sufficiently probed, despite the recent discovery of interesting ''orphan'' pathway members such as endoplasmic reticulum ion transporters (Kreiling et al, 2008) and evidence indicating the dorsalventral axis is established at the second cleavage (Gore et al, 2005). Moving forward will require increased collaboration among labs with expertise in specific pathways and model systems to cross-check their pathways in a wider variety of taxa, and remaining open to the idea that the origin problem is not yet solved.…”
Section: Major Open Issuesmentioning
confidence: 99%
“…These observations support the notion that the ICM is initially a mosaic of EPI and PE cells and suggest that an embryonic axis prepattern may exist as early as the blastocyst stage. Another interesting finding recently obtained in zebrafish suggests that a homologue of Nodal, squint (sqt), mRNA localizes to the future dorsal side of the embryo as early as the four-cell stage (Gore et al, 2005). Initially, maternal sqt mRNA is distributed evenly throughout the cytoplasm of the egg but, after fertilization, maternal sqt mRNA gradually becomes enriched in future dorsal cells.…”
Section: Formation Of the Anterior/ Posterior Axismentioning
confidence: 99%
“…Analysis of mutations that affect cyc and sqt has shown that these genes have overlapping functions in the embryo during mesoderm induction (Erter et al, 1998;Feldman et al, 1998;Long et al, 2003;Rebagliati et al, 1998a;Rebagliati et al, 1998b;Sampath et al, 1998). Loss of cyc function results in severe deficiencies in the ventral neural tube and in cyclopia, whereas sqt function is required for formation of the mesendoderm and dorsal structures (Erter et al, 1998;Feldman et al, 2000;Feldman et al, 1998;Gore et al, 2005;Hagos et al, 2007;Hatta et al, 1991;Rebagliati et al, 1998b;Sampath et al, 1998;Sirotkin et al, 2000;Tian et al, 2003). Spw regulates left-right asymmetry of the visceral organs during somitogenesis (Long et al, 2003).…”
Section: Introductionmentioning
confidence: 99%